Active Disturbance Rejection Control of Wearable Lower-Limb System Based on Reduced ESO - Nasir Ahmed Alawad; Amjad J. Humaidi; Abdulkareem Sh. Mahdi Al-Obaidi; Ahmed Sabah Alaraji (Indonesian Journal of Science and Technology, 2022)
Wearable robots are commonly used for rehabilitation and they are made to fit the human body to assist persons who are unable to help themselves. The design of controllers became necessary to enhance the dynamic motion of these exoskeleton systems when worn by patients. In this study, active disturbance rejection control (ADRC) with reduced-order extended state observer (RESO) has been proposed for motion control of exoskeleton knee-assisting device to eliminate the phase lag induced by full-order extended state observer (FESO). The design analysis of RESO-based ADRC has been presented and a computer simulation has been conducted to verify the effectiveness of the proposed controller. A comparison study has been made between ADRC based on RESO and that based on FESO in terms of transient and robustness characteristics. The simulated results showed that the RESO-based ADRC gives better transient and load rejection capabilities compared to the controller with FESO.